Ilam Tea: Peak season Capacity Confomance Practice in Processing Orthodox Tea - Pokharel, Hari Prasad (Tribhuvan University Journal, 2011)
Available with full text Key words: Ilam tea; Agriculture; Orthodox Tea Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 73-86 Uploaded date: 21 April, 2011